2014
DOI: 10.1159/000356325
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Size in Renal Cell Cancer in Relation to the Occurrence of Synchronous Metastatic Disease

Abstract: Objectives: To investigate the controversially discussed relationship between tumor size and the occurrence of primary synchronous metastatic disease in renal cell cancer (RCC). Patients and Methods: A consecutive RCC cohort of 2,058 patients (150 primary metastatic) who underwent surgery between 1995 and 2010 was investigated. Rates of synchronous metastases were calculated for stratified groups of tumor size. Uni- and multivariate logistic regression models were calculated for the correlation of tumor size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Zastrow et al [25] reported tumor size and ASA score as significant prognostic factor of metastasis after surgery, although their results did not reach significance in subgroup analysis of SRMs ≤ 4 cm. Takayama et al [26] also reported that symptom at diagnosis, CRP ≥ 0.4 mg/dl, tumor size ≥3.0 cm, histological grade 3, a sarcomatoid component, and microvascular invasion were independent risk factors for metastasis.…”
Section: Discussionmentioning
confidence: 90%
“…Zastrow et al [25] reported tumor size and ASA score as significant prognostic factor of metastasis after surgery, although their results did not reach significance in subgroup analysis of SRMs ≤ 4 cm. Takayama et al [26] also reported that symptom at diagnosis, CRP ≥ 0.4 mg/dl, tumor size ≥3.0 cm, histological grade 3, a sarcomatoid component, and microvascular invasion were independent risk factors for metastasis.…”
Section: Discussionmentioning
confidence: 90%
“…The relevance of the tumor size to RCC local advance or distant metastasis has been suggested by some literatures previously. A cohort study showed big tumor is inclined to metastasis [ 32 ]. In agree with this, the study of tumor size and metastasis in RCC patients from 1971–2005 in Iceland found that metastasis risk increased with increasing tumor size, but no linear relationship was found [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was 67.6 (35-87 years) with a mean BMI of 26.8 kg/m 2 (19.1-36.2 kg/m 2 ). The majority of the patients were male (31 men vs. 9 women) with a mean ASA score of 2.3 [2,3]. Six patients were operated on a single kidney situation, which were the only imperative cases in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Tumors are more frequent diagnosed at a lower stage and before symptoms such as pain or hematuria or synchronous metastases might imply a pathological process [1,2]. Consequently, nephron-sparing surgery in the sense of partial nephrectomy has gained importance in the treatment of renal masses.…”
Section: Introductionmentioning
confidence: 99%